Serum lipid profiles and post-stroke depression in acute ischemic stroke patients - Shen H (Dove Medical Press, 2019)
Huiping Shen,1,2,* Xinjie Tu,1,* Xiaoqian Luan,1 Yaying Zeng,1,2 Jincai He,1 Wenjie Tang21Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, People’s Republic of China; 2First School of Clinical Medicie, Wenzhou Medical University, Wenzhou, 325000, People’s Republic of China*These authors contributed equally to this work Purpose: Post-stroke depression (PSD) is a psychiatric complication after stroke that leads to poorer stroke outcomes. Recent observational studies have indicated that lipid profiles were associated with a higher risk of stroke and depression. This study aims to further explore the possible relationship between serum lipid profiles and the development of PSD.Methods: A total of 373 acute ischemic stroke patients were examined. Serum lipid profiles including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), total cholesterol (TC), apolipoprotein A1 (Apo A1) and apolipoprotein B (Apo B) were measured within 24 hrs of admission. Depression symptoms were assessed by the 17-item Hamilton Depression Scale (HAMD-17) at the one-month follow-up, and HAMD scores ≥7 indicated a diagnosis of PSD.Results: A total of 114 patients were diagnosed with PSD at the one-month follow-up, for a percentage of 30.6%. There were significant differences in HDL-C levels (P<0.001), LDL-C levels (P=0.002) and the LDL/HDL ratio (P<0.001) between the PSD and non-PSD groups, but no differences were observed in TGs, TC, Apo A1 or Apo B. Low serum HDL-C levels (r = −0.157, P<0.001) and elevated LDL-C levels (r =0.139, P=0.002) and the LDL/HDL ratio (r =0.227, P<0.001) were associated with HAMD scores. After adjusting for the NIHSS score, BI score, mRS score and alcohol consumption in the logistic analysis, low HDL-C levels and the highest quartile (≥3.07) of the LDL/HDL ratio were independently associated with the development of PSD (OR =0.250, 95% CI, 0.077–0.813, P=0.021 and OR =1.874, 95% CI, 1.050–3.347, P=0.034, respectively).Conclusion: Decreased levels of HDL-C and elevated levels of LDL/HDL ratio are associated with PSD. HDL-C and the LDL/HDL ratio are independent predictors of PSD.Keywords: lipid profiles, high-density lipoprotein cholesterol, LDL/HDL ratio, post-stroke depression